Validação de folhas detectoras OSL de CaF2 para aplicações em radiocirurgia - Torquato, Michele (2019)
Among all therapeutic modalities in radiotherapy, radiosurgery has gained prominence as an effective form of treatment associated with low morbidity and mortality. Particularly, Volumetric Modulated Arc Therapy (VMAT) technology provides treatment volume coverage preserving risk organs, with the benefit of rapid dose delivery. It allows more comfort and reducing movement during treatment execution. In radiosurgery, in addition to equipment quality testing, other controls are required to ensure delivery of the planned dose to each patient. Quality controls and dose measurements can be made using ionization chamber, radiochromic film, luminescent detectors and others. Among the dosimetric systems that employ luminescent detectors are those based on Optically Stimulated Luminescence (OSL). Due to the optical nature of the process, the main advantage is the possibility of re-evaluation of doses (rereading), evaluation of distribution and dose profile. Considering the need of accuracy and efficiency for small field dosimetry and the advantages of OSL detectors, this study compared the quality control done with ionization chamber during the planning of radiosurgery treatments (gold standard) with the quality control using OSL detector sheets of calcium fluoride (CaF2) based on Brazilian national fluorite. To validate quality control in radiosurgery using CaF2 OSL sheets, these were placed in the position of ionization chamber into the phantom, as routinely performed, to verify the planned hypofractioned doses of 300 cGy and 600 cGy and the treatment dose. Of 2100 cGy. For the prescribed dose of 2100 cGy, dose distribution and field profile were obtained using OSL detector sheets. Then, aiming validation of OSL sheets, it was performed the treatment, with the prescribed dose of 2100 cGy, in an anthropomorphic simulator, comparing the evaluated doses through detector sheets with those presented in the planning system. The evaluated doses, for each of the three values, along the length of the OSL detector strips are compatible with the values provided by the system and measured with the ionization chamber. In addition, it was possible to verify the dose distribution and field profile in radiosurgery with VMAT using OSL detector sheets. The obtained results validate the application of OSL detector sheets based on Brazilian natural fluorite in radiosurgery, indicating their application for dose distribution, quality control and dosimetry measurements in radiotherapy with high dose treatments.